Diagnostic accuracy of screening tools for silent aspiration in patients with dysphagia: a systematic review and meta-analysis - Sun, Wen-Jing; Cui, Wen-Yao; Jiang, Yan; Liu, Wen-Jie (Frontiers in Neurology, 2025)
BackgroundThe diagnosis and screening of silent aspiration are crucial for patients with dysphagia. This study aimed to synthesize the evidence and evaluate the diagnostic accuracy of screening tools for silent aspiration in patients with dysphagia.MethodsA comprehensive search of 6 databases including Pubmed, Web of Science, CINAHL, Cochrane Library, Scopus, and Embase was conducted from database inception to July 1st, 2024. Meta-analysis was performed on more than three studies. The bivariate mixed effect model was used to pool the sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). Narrative analysis was applied for studies that could not conduct meta-analysis.ResultsA total of nine studies were identified, which included six screening tools. Five of these screening tools for silent aspiration were analyzed descriptively. The meta-analysis was conducted to calculate the diagnostic accuracy of cough reflex test (CRT). The combined sensitivity and specificity of CRT were 0.65 (95% CI: 0.38–0.85) and 0.71 (95% CI: 0.63–0.79), respectively. The PLR, NLR, and DOR were 2.27 (95% CI: 1.49–3.47), 0.49 (95% CI: 0.24–0.99), and 4.68 (95% CI: 1.57–13.98), respectively. The area under the SROC curve was 0.73 (95% CI: 0.69–0.77).ConclusionThe videofluoroscopic swallowing study (VFSS) and flexible endoscopic evaluation of swallowing (FEES) remain the widely used gold standards for diagnosing silent aspiration. The CRT demonstrates moderate value in diagnosing and predicting silent aspiration. Further studies are needed to compare the diagnostic accuracy and predictive value of the remaining five screening tools for silent aspiration.Systematic review registrationIdentifier CRD42023493439.